Staying engaged : a qualitative study of the pursuits and desired of senior citizens after retirement - Nathan H.K Wong; Hon, Kai Yee (Universiti Malaysia Sabah, 2024)
Retirement, often seen as a peaceful stage of life, depends on how retirees utilize their time meaningfully. This study explores the activities and desires of retirees in Kuching, Sarawak, through 8 semi-structured interviews with Chinese respondents aged 65 to 86. The researchers adopted thematic analysis as our approach, and social interactions emerged as a significant element in the current study. However, the COVID-19 pandemic disrupted and reshaped the efforts related to social engagements. Despite economic activities, monetary gain is not a top priority; instead, retirees find satisfaction in artistic and cultural endeavors, prompting further inquiry. Our study also uncovers retirees' longings, revealing a desire for external support driven by empathy and a yearning for cultural experiences, indicating a desire to preserve cultural heritage. These findings lay a foundation for tailored activities for retirees and merit further investigation especially after retirement.